A text mining analysis of European banks' and insurers' disclosures on climate-related risks - Kraus, Anna (Risk Management and Insurance Review, 2024)
This paper empirically analyzes sustainability-related disclosures of listed European banks and insurance companies by focusing on transition risks, physical risks as well as stranded assets as a possible consequence of transition and physical risks. We employ a text mining analysis and apply a comprehensive keyword catalog to 142 firms. The dataset used for the analysis comprises 852 annual and 551 sustainability reports, covering a sample period from 2017 to 2022. Our results show that disclosure on climate-related risks considerably increases over the examined period, but that reporting on stranded assets is still in early stages. Moreover, European insurers report more on climate-related risks relative to the number of analyzed tokens than banks. Finally, statistical evidence suggests that larger banks and insurers with above-median market capitalization exhibit significantly more word hits on climate-related risks as compared to smaller firms.
CRIS-Team Scopus Importer:2024-11-29

Do sustainability attributes play a role for individuals’ decisions regarding unit-linked life insurance? A survey research on German private investors - Gatzert, Nadine; Kraus, Anna (Geneva Papers on Risk and Insurance: Issues and Practice, 2024)
The aim of this paper is to investigate the relevance of sustainable product attributes as compared to ongoing costs and risk–return profiles when individuals choose funds underlying unit-linked life insurances. Regarding sustainability attributes, we focus on the product classification according to the Sustainable Finance Disclosure Regulation as a European regulatory transparency standard, and on sustainable investment strategies. We conduct two choice-based conjoint analyses using a German panel for unit-linked life insurances as well as fund savings plans as a financial product comparison. We estimate the relative importance, part-worth utilities, and the marginal willingness to pay for changes in product attributes. Our results suggest that private investors of unit-linked life insurances value sustainable product attributes and that they result in a slightly higher marginal willingness to pay, but risk–return indicators and especially ongoing costs are currently more relevant. We find further indications that sustainability attributes are less relevant in the setting of a unit-linked life insurance as compared to a fund savings plans setting.
CRIS-Team Scopus Importer:2024-04-12
Keywords: D81; G11; G22; G40; G52; German private investors; Investment behavior; O16; Savings plans; SFDR; Sustainable funds; Unit-linked life insurance